Addressing Nigeria National Security Issues through Advance Technology (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper addresses the need for the adaption of advance technologies in the Nigeria national security. It considers current realities of the Nigerian national security system and practices, in contrast to what it can become and should be, if the proper advance technological tools and knowledge are so adapted. The work also queries the current paradigm of Nigerian internal and external security practices and processes, with its continuous default in yielding the needed result. These current practices of national security in Nigeria has proven to be less effective than required, this is because Nigerian national security system cannot continue in the same pattern and expect a different result. For the most part, the Nigerian external and internal security forces adopt an analogue system of practice and processes, which jeopardizes its chances of winning the war against national security threats and puts very serious strain on servicemen. The Nigerian security processes must now begin to wheel in the direction of the implementation of advance technologies in its fight against national security threats to at least 60% to 75% ratio. This will increases the nations chances of reigning over national security threats both internally and externally for the survival of the territorial integrity and sovereignty of the Nigerian State, while ensuring the security of lives, properties and peaceful coexistence within its borders.